The Roles of Nanoparticles in Stem Cell-Based Therapy for Cardiovascular Disease - Sun, Yuting; Lu, Yuexin; Yin, Li; Liu, Zhenjie (Frontiers in Bioengineering and Biotechnology, 2020)
Cardiovascular disease (CVD) is currently one of the primary causes of mortality and morbidity worldwide. Stem cell-based therapy with nanoparticles (NPs) can help us solve many problems we faced in current clinical practice because of their unique physical and chemical properties. Because of NPs’ special features, they are playing increasingly important roles in regulating stem cell behavior. In terms of cardiac disease, NPs can deliver gene in stem cells, track the stem cells in vivo for long-term monitoring, and enhance retention after their transplantation. The advantages of applying NPs in peripheral vascular disease (PVD) treatments include facilitating stem cell therapy, mimicking the extracellular matrix (ECM) and acting as a safe nonviral gene delivery tools. However, the main limitation of NPs is toxicity, which is related to their size, shape, aspect ratio, surface charge. Currently, there have been many animal models proving NPs’ potential in treating CVD but no extensive application of stem-cell therapy using NPs in clinical practice. In conclusion, NPs might have significant potential uses in clinical trials of CVD and human treatments in the future, thereby meeting the changing needs of individual patients worldwide.